Multiple micronutrient supplementation cost–benefit tool for informing maternal nutrition policy and investment decisions - Allison M. J. Verney; Jennifer F. Busch‐Hallen; Dylan D. Walters; Sarah N. Rowe; Zuzanna A. Kurzawa; Mandana Arabi (Maternal and Child Nutrition, 2023)
Abstract Antenatal multiple micronutrient supplementation (MMS) is an intervention that can help reach three of the six global nutrition targets, either directly or indirectly: a reduction in low birth weight, stunting, and anaemia in women of reproductive age. To support global guideline development and national decision‐making on investments into maternal nutrition, Nutrition International developed a modelling tool called the MMS cost–benefit tool to help users understand whether antenatal MMS is better value for money than iron and folic acid supplementation (IFAS) during pregnancy. The MMS cost–benefit tool can generate estimates on the potential health impact, budget impact, economic value, cost‐effectiveness and benefit–cost ratio of investing in MMS compared to IFAS in LMICs. In the 33 countries with data included in the tool, the MMS cost–benefit tool shows that transitioning is expected to generate substantial health benefits in terms of morbidity and mortality averted and can be very cost‐effective in multiple scenarios for these countries. The cost per DALY averted averages at US$ 23.61 and benefit–cost ratio ranges from US$ 41–US$ 1304: $1.0, which suggest MMS is good value for money compared with IFAS. With its user‐friendly design, open access availability, and online data‐driven analytics, the MMS cost–benefit tool can be a powerful resource for governments and nutrition partners seeking timely and evidence‐based analyses to inform policy‐decision and investments towards the scale‐up of MMS for pregnant women globally.